Signaling in 360° Desktop Virtual Reality Influences Learning Outcome and Cognitive Load - Albus, Patrick; Seufert, Tina (Frontiers in Education, 2022)
Learning with desktop virtual reality learning environments (DVR) can be highly visual and present many visual stimuli simultaneously. This can be distracting and require instructional support to help learners in their learning processes. The signaling principle could be a promising approach to support these processes, as signals can guide learners' attention to the relevant information (Mayer, 2005). The present study investigated the effects of signals in a 360° DVR on learning outcomes and cognitive load. In our between-subjects design, we examined a total of N = 96 participants who were randomly assigned to the signaling or non-signaling group. We hypothesized that the signaling group would achieve higher recall, comprehension, and transfer performance than the non-signaling group. We also expected that the signaling group would experience less extraneous cognitive load and higher germane cognitive load than the non-signaling group. The results show that learners who received signals in a DVR achieved significantly higher recall and comprehension scores than learners who did not receive signals. Transfer performance did not differ between groups. Participants in the signals group also experienced significantly lower extraneous cognitive load than participants in the non-signaling group. However, no differences in germane cognitive load were found between groups. These results suggest that learners in a DVR can be supported by signals in their learning processes while simultaneously helping to reduce unnecessary cognitive load.